Maintaining Direct Regional Head Elections, Solutions or Challenges? - Ratna Riyanti (Journal of Governance, 2022)
The discourse of simultaneous local elections in 2024 is still being debated by by-election and democracy observers. Based on Article 201 paragraph (8) of Law Number 10/2016 concerning the Election of Governors, Regents, and Mayors, simultaneous national voting for regional elections in all regions of Indonesia will be held in November 2024. This event, known as Pilkada, is being discussed by the government with the DPR and is nearing its end. One of the prominent debates is whether the Pilkada will be changed from where the Governor and the Regent/Mayor are elected directly through elections to where the Provincial DPRD elects the Governor. The Regent/Mayor is still elected through elections. Does the question arise whether the direct or indirect Pilkada is a solution or a challenge? Direct Pilkada means that the filling of regional head positions is carried out through a general election (election) or is elected directly by the people-voters. Indirect elections seem to mean that regional heads are elected not directly by the people's voters but by the Regional People's Representative Council (DPRD) or appointed (appointed) by officials above them. Does this paper examine whether the Pilkada, conducted directly or indirectly, is a solution to democracy in Indonesia, or is it a challenge?